New Model of Local Government Administrative Service in a New Normal Pattern of Behavior Era in Indonesia - Polyando, Petrus; Kartiw (International Journal of Criminology and Sociology, 2021)
This study departs from a new habitual adaptation movement that changes people's social interactions as a rational choice amid the threat of the Covid-19 outbreak. The purpose of this article is to test empirically that the current model of local government administrative services in the archipelagic sub-districts is very inefficient and less productive so that it has an impact on meeting the basic needs of the community comfortably and fairly. Furthermore, this study offers a new model for Duo-TM, namely Temu Muka dan Temu Mesin. This article shows the need for an empirical study in the development of a local government administrative service model to trace geographic difficulties and risks due to the Covid-19 outbreak. This is especially relevant if the author refers to the reasons for the massive change in various social dimensions and forces the adaptation of new habits. On the other hand, the era of the 4.0 industrial revolution places the power of technology and information as a means for innovating services that are comfortable, fast, inexpensive, and of high quality.